Improved Sensorless Speed Vector Control Of Induction Motor Drive Based On Synergetic Theory - REZGALLAH CHAIMA; KOUZI Kattia (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE: Département Électrotechnique, 2024)
The main objective of this memory is to enhance the performance of synergetic sensorless speed vector control of Induction Motor (IM). In the first part of this work, we have modeled the induction motor and its power supply consists mainly of voltage inverter controlled by current with hysteresis PWM, then we have presented the aspect of vector control applied to IM. In the second phase, two control strategies were proposed, namely fuzzy and synergetic vector control applied to the IM. Several numerical simulation results ofthe presented command were illustrated and commented on. In the last phase, in order to minimize the chattering phenomena, it was developedsensorless speed vector control of IM equipped with an improved adaptive sliding mode observer. The idea of proposed observer is replace the switching observer term of conventional adaptive sliding mode observer by smooth functionsand retain the benefits achieved by this later. The observer estimates the rotor flux components in the stationary reference frame by the IM measurement. The mechanical speed is estimated by adding a Lyapunov function. The performance and efficiency of the presented estimation algorithm were illustrated by simulation results.
Electric Control